Comparison of open and closed abdomen techniques for the delivery of intraperitoneal pemetrexed using a murine model. Issue 6 (22nd January 2018) - Badrudin, David; Sideris, Lucas; Perrault‐Mercier, Camille; Hubert, Julien; Leblond, François A.; Dubé, Pierre
Abstract : Background and Objectives: Pemetrexed is an appealing agent to use for cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (HIPEC). However, the optimal method of pemetrexed delivery still remains undefined. Using a murine model, we compared the use of open and closed abdomen techniques on the absorption of intraperitoneal (IP) pemetrexed in different compartments. Methods: Eleven Sprague‐Dawley rats were submitted to a fixed dose of IP pemetrexed (1000 mg/m 2 ) at a perfusion temperature of 40°C during 25 min according to two techniques: open and closed. At the end of perfusion, samples in different compartments were harvested and the concentrations of pemetrexed were measured by high performance liquid chromatography. Results: Absorption of IP pemetrexed in portal and systemic blood was significantly higher using the open compared to the closed abdomen technique (93.17 vs 52.50 µg/mL, P  < 0.001) and (76.26 vs 51.65 µg/mL, P  < 0.001), respectively. No difference was found between the two techniques on the peritoneal tissue concentration of pemetrexed (18.07 vs 19.17 µg/g, P  = 0.51). Conclusion: Peritoneal absorption of pemetrexed is not modified by the use of either technique. However, systemic concentrations of pemetrexed increased using the open technique, suggesting it could increase systemic toxicity.